The effect of aggregating bootstrap on the accuracy of neural network system for Islamic investment prediction - Nurul Hila Zainuddin (Tanjung Malim, 2021)
The effect of aggregating bootstrap on the accuracy of neural network system for Islamic investment prediction by Nurul Hila Zainuddin